PANCASILA SEBAGAI DASAR FILSAFAT ILMU DI INDONESIA - Putri, Nadia Desiana (JOURNAL OF SOCIAL, JUSTICE AND POLICY, 2025)
Pancasila, as the basis of the Indonesian state, not only acts as the nation's way of life, but also as a philosophical foundation in various fields of life, including science. This article discusses the role of Pancasila as the basis for the philosophy of science in Indonesia by looking at the relevance of Pancasila values ​​in the development of science, the formation of scientific paradigms and scientific ethics in Indonesia. Pancasila provides a foundation for the development of science rooted in human values, social justice and democracy, which reflects the personality of the Indonesian nation. Through understanding Pancasila, science in Indonesia can develop while maintaining harmony between rational and moral aspects.Pancasila, as the foundation of the Indonesian state, has a very important role in shaping the nation’s outlook on life, including in the field of science. As a philosophical basis that reflects noble values, Pancasila not only functions as a guideline in national and state life, but also provides direction in the development of science that is ethical, just and beneficial to society. In this context, Pancasila acts as a foundation for the philosophy of science which directs scientists to develop science that is not only based on rationality and objectivity, but also pays attention to moral, social and spiritual values. Each principle in Pancasila provides guidance in a scientific approach, such as respect for human dignity, the importance of social justice, and the use of knowledge for the common good. Therefore, Pancasila as the basic philosophy of science in Indonesia encourages the development of science that is inclusive, fair and supports the welfare of all Indonesian people, as well as supporting the creation of research and technology that is sustainable and beneficial to people’s lives. This article aims to explore the relevance of Pancasila in the philosophy of science in Indonesia and explore how Pancasila values ​​can be applied in the development of science and technology in Indonesia